2018
DOI: 10.1111/jpi.12477
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against defects induced by deoxynivalenol during mouse oocyte maturation

Abstract: Deoxynivalenol (DON) is one of the most prevalent fusarium mycotoxins in feedstuff and food. DON causes detrimental effects on human and animal reproductive systems by inducing oxidative stress and apoptosis. However, melatonin is a multifunctional endogenous hormone that plays crucial roles in the development of animal germ cells and embryos as a robust deoxidizer. In this study, we explored the effects of melatonin on the DON exposure mouse oocytes. Our in vitro and in vivo results showed that DON adversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 40 publications
9
61
0
Order By: Relevance
“…Melatonin has important physiological functions, such as the control of circadian rhythms, decrease in oral temperature, regulation of follicular development and reproductive activity, and activation of the immune system . Previous research reports found that melatonin exerts a protective function in mouse oocytes and porcine oocytes . Our results agree with previous studies which suggest that melatonin plays an important role in steroid hormone synthesis of GCs, however, the mechanism underlying how melatonin affects steroid hormone synthesis in GCs is unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Melatonin has important physiological functions, such as the control of circadian rhythms, decrease in oral temperature, regulation of follicular development and reproductive activity, and activation of the immune system . Previous research reports found that melatonin exerts a protective function in mouse oocytes and porcine oocytes . Our results agree with previous studies which suggest that melatonin plays an important role in steroid hormone synthesis of GCs, however, the mechanism underlying how melatonin affects steroid hormone synthesis in GCs is unclear.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, melatonin increased the global H3K9ac levels, reduced the H3K9me3 levels, and did not affected DNA methylation and hydroxymethylation in oocytes. Lan et al (2018) and Y. Zhang et al (2018) also proved that melatonin could restore abnormal epigenetic alterations induced by deoxynivalenol and MEHP in mouse and porcine oocytes.…”
Section: Discussionmentioning
confidence: 83%
“…A total of 2 μM DON was shown to affect the formation of the meiotic spindle in mouse oocytes ( Lan et al, 2018 ). While a recent study showed that 10 μM DON affected the morphology of pig ovaries with an ex vivo approach ( Gerez, Desto & Bracarense, 2017 ).…”
Section: Discussionmentioning
confidence: 99%